Preparation and characterization of Li1.167-xKxMn0.583Ni0·25O2 (x=0, 0.025, 0.05 and 0.075) as cathode materials for highly reversible lithium-ion batteries. (1st May 2020) - Liu, Cong; Wu, Manman; Guo, Zhaoxin; Luo, Xiangkai; Ji, Hongmei; Yang, Gang; Hou, Wenhua
Abstract: Lithium-rich cathode materials have the potential for applications in high energy lithium-ion batteries, but they suffer from a low rate performance and an inferior cycling stability. In this work, Li1.167- x K x Mn0.583 Ni0·25 O2 ( x  = 0, 0.025, 0.05 and 0.075) samples are synthesized and characterized. In addition, K + doping results in small perturbations in the crystal structure of Li1.167- x K x Mn0.583 Ni0·25 O2, such as the Li–O bond lengths, lattice parameters and the oxidation states of manganese, which effectively improves the lithium diffusion ability and hinders the detrimental interphase growth of the spinel phase during cycling. In a half-cell, Li1·117 K0·05 Mn0·583 Ni0·25 O2 (LK2MNO) with an optimized doping quantity of K + delivers the best capacities of 152.0 mAh g −1 after 100 cycles at a 1C rate and 82.9 mAh g −1 after 300 cycles at a 10C rate, in comparison with Li1·167 Mn0·583 Ni0·25 O2, which has a capacity of only 126.0 and 33.3 mAh g −1 . In the full-cell with graphite as the negative electrode, LK2MNO delivers an initial capacity of 249.9 mAh g −1 at a 0.1C rate and retains 90.8% of its initial capacity after 100 cycles. The surface chemical states of the positive electrode and negative electrodes after 100 cycles is studied by ex situ SEM and XPS measurements, and the results reveal that an appropriate K + doping amount effectively hinders the dissolution of Mn 2+ from the cathode material and decreases the decomposition of electrolytes to some degree. Graphical abstract: K + doping in Mn-based lithium-rich cathode materials improves the lithium diffusion ability and hinders the detrimental interphase growth of the spinel phase during cycling. In full cell, the LK2MNO sample delivers an initial capacity of 249.9 mAh g −1 at a 0.1C rate and retains 90.8% of its initial capacity after 100 cycles. The surface chemical state of the positive and negative electrodes after 100 cycles reveal that K + doping effectively suppresses side reactions and electrolyte decomposition. Image 1 Highlights: K + doping results in small perturbations in Li1.167- x K x Mn0.583 Ni0·25 O2 structure. Potassium doping decreases the detrimental interphase growth of spinel phase during cycling. Expanding interlayer spacing by K + provide fast conductive channel for Li + diffusion. LK2MNO delivers 249.9 mAh g −1 and remains 90.8% of initial capacity after 100 cycles. K + doping suppresses side reactions and electrolyte decomposition during cycling.